Adherence to lifestyle modifications after a cardiac rehabilitation program and endothelial progenitor cells - Cesari, Francesca; Marcucci, Rossella; Gori, Anna Maria; Burgisser, Costanza; Francini, Sara; Roberts, Anna Teresa; Sofi, Francesco; Gensini, Gian Franco; Abbate, Rosanna; Fattirolli, Francesco (Thrombosis and Haemostasis, 2014)
An increase of endothelial progenitor cells (EPCs) among acute myo-cardial infarction (AMI) patients participating in a cardiac rehabilitation (CR) program has been reported, but no data on the impact of adherence to lifestyle recommendations provided during a CR program on EPCs are available. It was our aim to investigate the effect of adherence to lifestyle recommendations on EPCs, inflammatory and functional parameters after six months of a CR program in AMI patients. In 110 AMI patients (90 male/20 female; mean age 57.9 ± 9.4 years) EPCs, high sensitivity C-reactive protein (hsCRP), N-terminal pro-brain natriuretic peptide (NT-ProBNP) levels, and cardiopulmonary testings were determined at the end of the CR (T1) and at a six-month follow-up (T2). At T2 we administered a questionnaire assessing dietary habits and physical activity. At T2, we observed a decrease of EPCs (p<0.05), of hsCRP (p=0.009) and of NT-ProBNP (p<0.0001). Patient population was divided into three categories by Healthy Lifestyle (HL) score (none/low, moderate and high adherence to lifestyle recommendations). We observed a significant association between adherence to lifestyle recommendations, increase in EPCs and exercise capacity between T1 and T2 (Δ EPCs p for trend <0.05; ΔWatt max p for trend=0.004). In a multivariate logistic regression analyses, being in the highest tertile of HL score affected the likelihood of an increase of EPC levels at T2 [OR (95% confidence interval): 3.36 (1.0–10.72) p=0.04]. In conclusion, adherence to lifestyle recommendations provided during a CR program positively influences EPC levels and exercise capacity.
Keywords: Lifestyle modifications; endothelial progenitor cells; cardiac rehabilitation; healthy lifestyle score